Succinate Dehydrogenase B (SDHB) Immunohistochemistry for the Evaluation of Muscle Biopsies. Issue 9 (October 2017) - Punsoni, Michael; Mangray, Shamlal; Lombardo, Kara A.; Heath, Nancy; Stopa, Edward G.; Yakirevich, Evgeny
Abstract : Succinate dehydrogenase (SDH) is a key mitochondrial enzyme complex composed of 4 subunits. SDH histochemistry is routinely utilized in the assessment of muscle biopsies to reveal underlying pathology such as subsarcolemmal mitochondrial aggregates. In this study, we evaluated the utility of succinate dehydrogenase B (SDHB) immunohistochemistry (IHC) in 27 muscle biopsies, including 13 mitochondrial myopathies (MMs), 9 inflammatory myopathies, and 5 controls. SDHB IHC was performed on formalin-fixed, paraffin-embedded tissue sections with a mouse monoclonal antibody (Abcam 21A11AE7) in parallel with histochemical SDH stains on a fresh-frozen tissue. In all muscle biopsies, SDHB IHC exhibited granular immunoreactivity and highlighted the dark type 1 and lighter type 2 staining pattern observed by histochemistry. In all cases of MM, SDHB IHC showed subsarcolemmal granular aggregates involving the entire periphery of the fibers that were more distinct than those seen by SDH histochemistry. In 3 extraocular muscle biopsies, SDHB immunoreactive speckles of various sizes were distributed throughout the entire sarcoplasm that were more prominent than those seen on SDH histochemistry. Subsarcolemmal and cytoplasmic granular aggregates seen on SDHB IHC correlated with mitochondrial pathology on electron microscopy. In cases of inflammatory myopathy, there was diffuse sarcoplasmic SDHB immunoreactivity in degenerating fibers, but no evidence of subsarcolemmal aggregates. This study demonstrates that SDHB IHC is highly sensitive and specific in the identification of MM. The automation, reproducibility, and cost efficiency of SDHB IHC offer advantages over the labor-intensive histochemical method requiring frozen sections. As this technique is performed on formalin-fixed, paraffin-embedded tissues, it can be easily applied for retrospective studies.